Behavioural impacts of Advanced Driver Assistance Systems–an overview - Brookhuis, Karel A.; de Waard, Dick; Janssen, Wiel H. (European Journal of Transport and Infrastructure Research, 2001)
The purpose of Advanced Driver Assistance Systems (ADAS) is that driver error will be reduced or even eliminated, and efficiency in traffic and transport is enhanced. The benefits of ADAS implementations are potentially considerable because of a significant decrease in human suffering, economical cost and pollution. However, there are also potential problems to be expected, since the task of driving a ordinary motor vehicle is changing in nature, in the direction of supervising a (partly) automated moving vehicle.